La aplicación de las nuevas tecnologías de la información y comunicación con énfasis en internet y su influencia en el proceso de enseñanza - aprendizaje de la matemática en los estudiantes del octavo, noveno y décimo años de educación general básica del instituto superior tecnológico Daniel Álvarez Burneo, de la parroquia El Valle, ciudad y provincia de Loja, período lectivo 2012 -2013. Lineamientos alternativos - Gonzaga Rivas, Jhon Fredy (2015)
This thesis: THE APPLICATION OF NEW INFORMATION TECHNOLOGY AND COMMUNICATION WITH EMPHASIS ON INTERNET AND ITS INFLUENCE ON THE TEACHING - LEARNING OF MATHEMATICS IN THE STUDENTS OF EIGHTH, NINTH AND TENTH YEAR OF BASIC EDUCATION INSTITUTE SUPERIOR GENERAL TECHNOLOGY DANIEL ALVAREZ BURNEO, PARISH EL VALLE CITY AND PROVINCE OF LOJA, LECTIVO PERIOD 2012 -2013. ALTERNATIVE GUIDELINES. Its general objective is to determine the impact of the application of new technologies of information and communication with emphasis on the Internet, by teachers and students in the process of teaching - learning of mathematics of students Eighth, Ninth and Ten Years of Basic General Education ISTDAB, Loja from the city of during the academic year 2012 - 2013; specific objectives: determine the level of application of new information technologies and communication with emphasis on the Internet by teachers during the process of teaching - learning of mathematics in the Eighth, Ninth and Tenth Years of General Education Basic of ISTDAB. Set the main causes that determine the low level of use of new information technologies and communication with emphasis on the Internet by teachers during the process of teaching - learning of mathematics in the Eighth, Ninth and Tenth Year Basic General Education ISTDAB. The present research was conducted through technical methods and tools that are employed in the ICT knowledge based the following procedure: it began with the collection of information, to eighth, ninth, and tenth year of basic general education comprised of 313 students and 9 math teachers. This research is conducted in the educational field proposes a curriculum innovation for teachers in the area of mathematics use the Technologies of the Information and Communication with emphasis on the Internet in the process of teaching - learning, the application of tools multimedia where the teacher turn the classroom into an interactive room, and research. According to the research study was able to demonstrate that 72% of students use the internet for fun as an element of distraction and entertainment, especially in access that they have to so-called social networks and 11% of students to good use right to grant the internet for learning math. The end of the investigation is concludes and recommended guide students on the proper use of the internet by accessing different web pages more efficient and productive in learning math, , also teachers give prominence on the handling of the Internet in the process teaching - learning inside and outside the classroom.